Agro-food exports variety from the Central and Eastern European countries - Štefan Bojnec; Imre Fertő (Agricultural Economics (AGRICECON), 2012)
This paper analyses the agro-food exports variety from twelve Central and Eastern European countries (CEECs) to the European Union (EU) during the years 1995-2007. The panel regression models explain the agro-food exports by its previous year, income in the importing EU countries, and measure of agro-food export product variety, while the real exchange rate appreciation of the CEEC currencies has negatively influenced agro-food exports. The EU enlargement with the reduction in agricultural protection and the borderless single market has induced agro-food export increases in primary agricultural produce and intermediate food-processed products, but less in higher value-added food-processed differentiated products. The impact of increased number of CEECs agro-food product varieties on agro-food export to the EU is positive.